2003
DOI: 10.1177/0886260503256841
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Validation of the Self-Appraisal Questionnaire with a Maximum-Security Psychiatric Population

Abstract: The Self-Appraisal Questionnaire (SAQ) is a 72-item, self-report measure designed to predict recidivism, supervision violations, and related behaviors among nonmentally disordered Canadian federal offenders. In the present article, the authors demonstrate that the SAQ maintains satisfactory predictive validity on cross-validation with a high-risk correctional psychiatric sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…To date, at least 20 studies have been published, as well as graduate theses, which have demonstrated more than adequate reliability and concurrent, construct, and predictive validities of the SAQ with male offenders over 2-, 5-, and 9-year follow-up periods (e.g., Loza, Dhaliwal, Kroner, & Loza-Fanous, 2000;Loza, MacTavish, & Loza-Fanous, in press). General findings from these studies indicated (a) prospective recidivism studies, involving Canadian male federal incarcerates have yielded outcome correlations numerically (albeit not in every case significantly) higher for the SAQ than other commonly used actuarial instruments (Kroner & Loza, 2001;Loza & Green, 2003;Loza & Loza-Fanous, 2001); (b) validity of the SAQ has been demonstrated for use with mentally disordered male offenders (Villeneuve, Oliver, & Loza, 2003), offenders from different countries (Australia, Canada, England, Singapore, South Africa, Spain, and United States), offenders with different ethnic backgrounds (Ballesteros, 2005;Loza, Conley, & Warren, 2004;Loza, Cumbleton, et al, 2004;Prinsloo, in press), female offenders (Loza, Neo, Shahinfar, & Loza-Fanous, 2005), and young offenders (Hemmati, 2004); (c) the SAQ has shown promise for prediction of institutional adjustment; (d) support was shown for the SAQ's usefulness in program assignment for male offenders (Loza & Loza-Fanous, 2003); and (e) there is evidence of a robust predictive validity of SAQ, after controlling for social desirability issues contaminants (Loza, Loza-Fanous, & Heseltine, in press;Mills, Loza, & Kroner, 2003). Finally, readers interested in the SAQ literature should refer to the SAQ manual (Loza, 2005), as the Mitchell and MacKenzie article was quite careless in improperly referencing almost all of the SAQ studies and not accurately reporting findings found from previous SAQ studies (e.g., in the Loza, Cumbleton, et al, 2004, study correlations between the SAQ subscales did not range between .43 and .89).…”
Section: Discussionmentioning
confidence: 88%
“…To date, at least 20 studies have been published, as well as graduate theses, which have demonstrated more than adequate reliability and concurrent, construct, and predictive validities of the SAQ with male offenders over 2-, 5-, and 9-year follow-up periods (e.g., Loza, Dhaliwal, Kroner, & Loza-Fanous, 2000;Loza, MacTavish, & Loza-Fanous, in press). General findings from these studies indicated (a) prospective recidivism studies, involving Canadian male federal incarcerates have yielded outcome correlations numerically (albeit not in every case significantly) higher for the SAQ than other commonly used actuarial instruments (Kroner & Loza, 2001;Loza & Green, 2003;Loza & Loza-Fanous, 2001); (b) validity of the SAQ has been demonstrated for use with mentally disordered male offenders (Villeneuve, Oliver, & Loza, 2003), offenders from different countries (Australia, Canada, England, Singapore, South Africa, Spain, and United States), offenders with different ethnic backgrounds (Ballesteros, 2005;Loza, Conley, & Warren, 2004;Loza, Cumbleton, et al, 2004;Prinsloo, in press), female offenders (Loza, Neo, Shahinfar, & Loza-Fanous, 2005), and young offenders (Hemmati, 2004); (c) the SAQ has shown promise for prediction of institutional adjustment; (d) support was shown for the SAQ's usefulness in program assignment for male offenders (Loza & Loza-Fanous, 2003); and (e) there is evidence of a robust predictive validity of SAQ, after controlling for social desirability issues contaminants (Loza, Loza-Fanous, & Heseltine, in press;Mills, Loza, & Kroner, 2003). Finally, readers interested in the SAQ literature should refer to the SAQ manual (Loza, 2005), as the Mitchell and MacKenzie article was quite careless in improperly referencing almost all of the SAQ studies and not accurately reporting findings found from previous SAQ studies (e.g., in the Loza, Cumbleton, et al, 2004, study correlations between the SAQ subscales did not range between .43 and .89).…”
Section: Discussionmentioning
confidence: 88%
“…Prospective recidivism studies involving Canadian federal incarcerates have yielded outcome correlations numerically (albeit not in every case significantly) higher than those produced by other commonly used actuarial instruments (Kroner & Loza, 2001;Loza & Green, 2003;Loza & Loza-Fanous, 2001). This result has also been found for offenders who are mentally disordered (Villeneuve, Oliver, & Loza, 2003). Other research has demonstrated the usefulness of the SAQ for the prediction of institutional adjustment and has provided support for the SAQ as a means of program assignment (Loza & Loza-Fanous, 2002).…”
Section: Methodsmentioning
confidence: 93%
“…Items included in the SAQVAL subscale are included in the predictive subscales. Previous research indicates that the SAQ could be used with all offenders and attests to the psychometric properties of the SAQ on Canadian offenders as well as its validity on offenders from other countries (see Kroner & Loza, 2001;Loza, Cumbleton, Shahinfar, Neo, Evans, Conley, & Summers, in press;Loza, Dhaliwal, Kroner, & Loza-Fanous, 2000;Loza & Green, 2003;Loza, Loza, Conley, & Warren, in press;Loza & LozaFanous, 2000;Loza & Loza-Fanous, 2001;Loza & Loza-Fanous, 2002;Loza & Loza-Fanous, in press;Mills, Loza, & Kroner, in press;Villeneuve, Oliver, & Loza, 2003).…”
Section: Methodsmentioning
confidence: 96%